2007
DOI: 10.1021/bc7002617
|View full text |Cite
|
Sign up to set email alerts
|

99mTc-maEEE-ZHER2:342, an Affibody Molecule-Based Tracer for the Detection of HER2 Expression in Malignant Tumors

Abstract: Detection of HER2-overexpression in tumors and metastases is important for the selection of patients who will benefit from trastuzumab treatment. Earlier investigations showed successful imaging of HER2-positive tumors in patients using indium- or gallium-labeled Affibody molecules. The goal of this study was to evaluate the use of (99m)Tc-labeled Affibody molecules for the detection of HER2 expression. The Affibody molecule Z(HER2:342) with the chelator sequences mercaptoacetyl-Gly-Glu-Gly (maGEG) and mercapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
99
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 102 publications
(108 citation statements)
references
References 36 publications
9
99
0
Order By: Relevance
“…Apparently, incorporation of the triglutamyl spacer reduced the on-rate of the binding, which caused increase of the dissociation constant from 49 pM for FBO-PEP4313 to 180 pM for FBO-E 3 -PEP4313. This was not entirely unexpected, as N-terminal modification has earlier caused some modulation of affinity of Affibody molecules 34,38 . However, our recent study 39 Reduction of the renal uptake was an interesting effect of the spacer.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Apparently, incorporation of the triglutamyl spacer reduced the on-rate of the binding, which caused increase of the dissociation constant from 49 pM for FBO-PEP4313 to 180 pM for FBO-E 3 -PEP4313. This was not entirely unexpected, as N-terminal modification has earlier caused some modulation of affinity of Affibody molecules 34,38 . However, our recent study 39 Reduction of the renal uptake was an interesting effect of the spacer.…”
Section: Discussionmentioning
confidence: 80%
“…Tc at the N-terminus by increasing the hydrophilicity of the peptide-based chelators via incorporation of glutamyl residues 34,35 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, different chemistry was used for conjugation of the DOTA chelator. Earlier experience with Affibody molecules has suggested that even smaller changes in composition (substitution of one to three amino acids) could cause appreciable differences in biodistribution, such as the level of hepatic uptake [25,26] or percentage of hepatobiliary excretion [27][28][29]. Moreover, coupling of different nuclides using the same chelator could cause differences in organ uptake and blood clearance rate of Affibody molecules [21,29,30].…”
Section: Discussionmentioning
confidence: 99%
“…in DCM was added (40 min) to the peptide-resin for specific acylation, followed by deprotonation and cyclization of the linker with 0.5 M DIEA in DCM [28].…”
Section: General Procedures Of Z Her2:342min Synthesismentioning
confidence: 99%
“…These conjugates include affitoxin [101], pseudomonas exotoxin [102,103], ricin A chain [104], various probes (radioactive and nonradioactive) [104][105][106][107][108][109][110][111][112], photosensitizers [113][114][115], RNAse [116,117], cytokines [118] or chemotherapeutic agents [119][120][121][122]. A Phase II study of a novel future science group HER2/neu: an increasingly important therapeutic target.…”
Section: Pertuzumabmentioning
confidence: 99%